COT-TT vaccine attenuates cocaine-seeking and cocaine-conditioned place preference in rats - Susana Barbosa-Méndez; Maura Matus-Ortega; Ricardo Hernandez-Miramontes; Alberto Salazar-Juarez (Taylor & Francis Group, 2024)
ABSTRACTVaccination active, promising alternative immunological strategy to treat of CUD. Various models of cocaine vaccines have been evaluated in animals and humans with relative success. In this sense, it is necessary to improve or optimize the cocaine vaccines already evaluated. Our laboratory previously reported the efficacy of the tetanus toxoid-conjugated morphine vaccine (M6-TT). The M6-TT vaccine can generate high titers of antibodies and reduce heroin-induced behavioral effects in rodents. So, it would be plausible to assume that if we modify the M6-TT vaccine by changing the hapten and maintaining the rest of the structural elements of the vaccine, we will maintain the properties of the M6-TT vaccine (high antibody titers). The objective of this study was to determine whether the antibodies generated by a tetanus toxoid-conjugated cocaine vaccine (COC-TT) can recognize and capture cocaine and decrease the cocaine-induced reinforcing effects. Male Wistar rats were immunized with the COC-TT. A solid-phase antibody-capture ELISA was used to monitor antibody titer responses after each booster dose in vaccinated animals. The study used cocaine self-administration and place-preference testing to evaluate the cocaine-reinforcing effects. The COC-TT vaccine could generate high levels of anti-cocaine antibodies. The antibodies reduced the cocaine self-administration and cocaine place preference. In addition, they decreased the cocaine-induced Fos protein expression. These findings suggest that the COC-TT vaccine generates a robust immunogenic response capable of reducing the reinforcing effects of cocaine, which supports its possible future use in clinical trials in patients with CUD.